Aesthetic Perception (On the Aesthetic Theory by V. Seseman) - Rastenis, Kęstutis (Problemos, 1982)
An organic and relational character of V. Seseman’ (1884-1963) theory is revealed. The theory is seen as based on the dialectic methodology, searching for specific (as well as objective) factors of aesthetic perception. The theory proceeds in two directions: the former factors are found both in object of an aesthetic perception and in the subject itself – through aesthetic perceptions, namely, in his acts directed to the concrete sensuous expressive unity of the object. Thus, V. Seseman has creatively used the theory of intentionality. An attempt is made towards extending V. Seseman’s theory to the contemporary problematics of aesthetic perception, which are very complicated.